Red raspberry (Rubus ideaus) supplementation mitigates the effects of a high-fat diet on brain and behavior in mice. (3rd June 2021) - Carey, Amanda N.; Pintea, Giulia I.; Van Leuven, Shelby; Gildawie, Kelsea R.; Squiccimara, Laura; Fine, Elizabeth; Rovnak, Abigail; Harrington, Mark
ABSTRACT: Objectives: Research has shown that berries may have the ability to reverse, reduce, or slow the progression of behavioral dysfunction associated with aging and neurodegenerative disease. In contrast, high-energy and high-fat diets (HFD) may result in behavioral deficits like those seen in aging animals. This research examined whether red raspberry ( Rubus ideaus ) mitigates the effects of HFD on mouse brain and behavior. Methods: Eight-week-old mice consumed a HFD (60% calories from fat) or a control diet (CD) with and without 4% freeze-dried red raspberry (RB). Behavioral tests and biochemical assays of brain tissue and serum were conducted. Results: After 12 weeks on the diets, mice fed CD and HFD had impaired novel object recognition, but mice on the RB-supplemented diets did not. After approximately 20 weeks on the diets, mice fed HFD + RB had shorter latencies to find the escape hole in the Barnes maze than the HFD-fed mice. Interleukin (IL)-6 was significantly elevated in the cortex of mice fed HFD; while mice fed the CD, CD + RB, and HFD + RB did not show a similar elevation. There was also evidence of increased brain-derived neurotrophic factor (BDNF) in the brains of mice fed RB diets. This reduction in IL-6 and increase in BDNF may contribute to the preservation of learning and memory in HFD + RB mice. Conclusion: This study demonstrates that RB may protect against the effects HFD has on brain and behavior; however, further research with human subjects is needed to confirm these benefits.